セールロンダーネ サンチ セイブ ノ チケイ ト コウキ シンセイダイ ノ ヒョウショウ ヘンドウ - 森脇, 喜一; モリワキ, キイチ; 平川, 一臣; ヒラカワ, カズオミ; Moriwaki, Kiichi; Hirakawa, Kazuomi (1992)
P(論文) セールロンダーネ山地西部には大規模な氷食地形が発達し, 風化度の異なる氷河堆積物に覆われるところが少なくない。表面が著しく風化した鮮新世のティルは現氷床上100m以上の山頂平坦面や氷食ベンチ上にみられるが, 一部は現氷床表面より低いドライバレーにも存在する。鮮新世のティルの多くは最大100mにも達する厚いティルである。山頂平坦面や氷食ベンチは, ティルに覆われていない部分もまた著しく風化している。更新世前∿中期と推定されるティルは少量で, 現氷床上約100mの山腹に小規模なラテラルモレーンを形成しているにすぎない。更新世後期以後のティルは氷河上ティルで, 現氷床表面上10m以下にモレーン原を形成している。鮮新世の氷床は温暖氷河で, 大量のティルを生産し氷食谷を形成して山地をいくつかの山塊に分割した。かつて山地の大部分を覆った氷床は鮮新世中期後大きく後退し, 鮮新世末期には現在見られる山塊を氷床上に出現させた。この後退期に最も後退した氷床表面は現在のそれより低くなったと推定される。更新世になって寒冷氷河となった氷河が再進出して, 小規模なラテラルモレーンを形成した。その後, 氷床は衰退して数万年前までに現在とほぼ同レベルに至り, 以後顕著な氷床変動はないらしい。最後の後退期に氷床表面が現在より低くなった時期があったかどうかは判らないが, 現在より温暖な環境があった。 The western Sør-Rondane Mountains with the exception of several high peaks were once covered by the ice sheet. The mountains are in some places covered with tills weathered in various degrees. Heavily weathered ground including Pliocene till is found on flat-topped surfaces of the mountains and glacial benches about 100m higher than the present ice surface. Heavily weathered ground is found also in an ice-free valley, bottom of which is lower than surrounding ice surface. Tills of the early to middle Pleistocene are small in quantity, and form only small lateral moraines on the mountain flanks about 100m higher than the present ice surface. Since the late Pleistocene, supraglacial tills have formed moraine fields around the mountains less than 10m above the present ice surface. The Pliocene temperate ice sheet produced, transported and deposited a large quantity of tills, and eroded the valley systems dividing the mountains into several blocks. The ice sheet shrank and most part of the mountains emerged from ice by the latest Pliocene. The lowest level of the ice sheet during this deglaciation was probably lower than that of the present day. The temperate ice sheet changed into cold one probably in early Pleistocene, and re-advanced up to about 100m higher than the present ice surface. Subsequently, the ice sheet retreated again to about 10m higher than the present level by several tens of thousand years ago. Then, ...